Patient Engagement’s Influence On Brand Image As A Mediator To Strengthen Revisit Intention - Kharisma Berlian Sjukri; Rokiah Kusumapradja; Erry Yudhya Mulyani (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2025)
The transformation of medical services in Indonesia from a disease-centered model to a patient-centered model has created intense competition among medical institutions. At one of the Maternal and Child Hospitals in Jakarta, a decline in visits from Non-BPJS patients indicates the need for a deeper understanding of the factors influencing patients' intentions to revisit. This study aims to analyze the influence of patient involvement and patient experience on the intention to revisit the hospital, with the mediation of the hospital's brand image. A quantitative approach with a cross-sectional design was used in this study. Data were collected through questionnaires from 119 Non-BPJS patients in the Outpatient Unit. Data analysis was conducted using PLS-SEM with the Smart-PLS program. The results showed that patient involvement and patient experience significantly influenced the intention to revisit, with the hospital's brand image serving as a strong mediator. Enhancing patient involvement, positive experiences, and a strong brand image can significantly increase patients' intention to return to the Maternal and Child Hospital in Jakarta.